Method for extracting lithium from electrolytic aluminum waste through mechanical strengthening and mechanical strengthening leaching kettle
Selective leaching and two-stage removal through mechanically strengthened leaching kettle, combined with lithium carbonate preparation, solve the problems of low lithium leaching rate and high cost in the prior art, and achieve efficient and economical lithium recycling and battery-grade lithium carbonate preparation.
Patent Information
- Application Number
- CN202411750435.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-04-11
AI Technical Summary
The leaching rate of lithium in the existing electrolytic aluminum waste slag extraction technology is low, the environment is unfriendly, and a large amount of sulfuric acid and sodium hydroxide are required, which leads to high costs and high operational difficulty.
Selective leaching is performed by mechanically strengthened leaching kettle, controlling the leaching conditions to selectively extract lithium, limiting the leaching of impurities such as aluminum and iron, and improving the recovery of lithium through two-stage impurity removal and lithium carbonate preparation processes.
The leaching rate of lithium is significantly improved to reach more than 95%, reducing the processing difficulty and cost, reducing the use of impurity removal alkalis, and realizing the preparation of battery-grade lithium carbonate.
Smart Images

Figure CN119800102A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of extraction and utilization of lithium-containing waste from electrolytic aluminum, and in particular to a method for mechanically strengthening lithium extraction from electrolytic aluminum waste and a mechanically strengthened leaching kettle. Background Art
[0002] In recent years, the country has introduced a series of policies to encourage the development of new energy and energy storage industries. Many leading companies such as CATL, BYD, and Guoxuan High-tech have emerged in the industry, leading my country's new energy industry to the forefront of the world. The development of the new energy industry has also driven the layout of lithium resources and the development and continuous improvement of lithium extraction technology.
[0003] The electrolytic aluminum industry has formed an aluminum production system including Aluminum Corporation of China, Guangxi Apple Aluminum, and Nanping Aluminum. With the economic development in recent years, the number and scale of enterprises have continued to grow and expand, and the output of electrolytic aluminum waste slag has continued to increase. Electrolytic aluminum waste slag contains a certain amount of lithium and cryolite. Due to the rise in lithium prices, a lot of research has been carried out on the extraction and utilization technology of lithium in aluminum slag in recent years. Companies such as Polyfluoro and Xinjiang Production and Construction Corps have carried out industrial layout, which can save a lot of lithium and aluminum resources.
[0004] For example, Chinese patent application number 2022113448491 discloses a method and equipment for recovering electrolytic aluminum waste slag, in which the electrolytic aluminum waste slag is slurried with sulfuric acid for sulfate roasting, the roasted material is hydrolyzed, alkali is added to the filtered solution to produce aluminum hydroxide precipitate, sodium carbonate is added to the filtrate to form sodium sulfate, and the recovered hydrogen fluoride, aluminum hydroxide, and sodium sulfate are synthesized into cryolite and sold to the electrolytic aluminum plant. This method uses sulfuric acid roasting to treat electrolytic aluminum waste slag to synthesize cryolite, and does not recover the lithium contained in the waste slag, and it also contains a small amount of other impurities such as iron that have not been treated. In addition, sulfuric acid roasting has high requirements for equipment.
[0005] The Chinese patent application number 2023107040418 discloses a process for improving the lithium leaching rate in the difficult-to-leach aluminum electrolytic waste slag, which comprises the following steps: preparing 10L of 5% aluminum chloride solution, adding 10g of waste slag to every 100ml of aluminum chloride solution, adding 1kg of waste slag to control the end point pH value to 3, leaching for 2 hours at room temperature, filtering and washing the filter residue, the filter residue is mainly impurities such as carbon, and the filtrate enters the impurity removal enrichment and purification process. The present invention uses an aluminum salt solution to dissolve the lithium sodium cryolite in the difficult-to-leach aluminum electrolytic waste slag, so that the lithium therein can be converted into lithium chloride or lithium sulfate, etc., thereby improving the lithium leaching rate in the difficult-to-leach aluminum electrolytic waste slag, and effectively solving the problem of low lithium leaching rate and environmental unfriendliness in the existing recovery process. The method uses aluminum chloride as a dissolving medium, and the leaching solution contains extremely high aluminum. Although the lithium leaching rate is high, it affects the recovery of lithium.
[0006] In addition, for the electrolytic aluminum waste slag with very high sodium and aluminum content and nearly half carbon, the amount of sulfuric acid and sodium hydroxide required to extract all the aluminum and lithium is very large, the amount of sodium sulfate crystallization is large, and the presence of carbon will lead to a large amount of precipitated slag and poor precipitation and filtration properties, affecting the total recovery rate of lithium. Therefore, it is necessary to develop a simpler, economical and effective method for extracting lithium from electrolytic aluminum slag to solve the above problems. Summary of the invention
[0007] Therefore, in order to solve the problems existing in the prior art, the present invention provides a method for mechanically strengthening lithium extraction from electrolytic aluminum waste and a mechanically strengthened leaching kettle. The method selectively extracts lithium from waste aluminum slag by controlling the leaching conditions, while limiting the leaching of impurities such as aluminum and iron in the slag. Lithium sulfate is further used to prepare lithium carbonate, which specifically includes the following steps:
[0008] Step 1: crushing the electrolytic aluminum waste with a carbon content of more than 45% and an aluminum content of more than 10 times the lithium content;
[0009] Step 2: calcining the crushed electrolytic aluminum waste at a high temperature of 550-1600°C for 0.5-5h to remove the carbon therein, and then cooling and coarse grinding to a particle size of 1-5mm to obtain a decarbonized material;
[0010] Step 3: subjecting the decarbonized material to mechanical enhanced acid leaching: finely grinding and selectively leaching the decarbonized material in a mechanical enhanced leaching kettle, and filtering to obtain a leachate and a leaching residue;
[0011] Step 4: performing two-stage impurity removal, wherein the first stage impurity removal process is: adding an oxidant to the leaching solution, then adding alkali to adjust the pH value to 4.5-5.0, filtering to obtain a filtrate and a filter residue; the second stage impurity removal process is: adding a decalcifying agent to the filtrate, then adding alkali to adjust the pH value to 12.0-13.0, filtering to obtain a lithium-containing filtrate and an impurity filter residue;
[0012] Step 5: heating and concentrating the lithium-containing filtrate, and then freezing and crystallizing it to obtain a denitrified liquid;
[0013] Step 6: adding sodium carbonate solution to the denitrified liquid under heating conditions, precipitating and filtering to obtain crude lithium carbonate;
[0014] Step 7: Dissolve the crude sodium carbonate in pure water and introduce CO2 gas into the solution. When the crude sodium carbonate is completely dissolved, filter it precisely to obtain a lithium carbonate solution. Heat, crystallize, filter, wash and dry to obtain battery-grade lithium carbonate.
[0015] Furthermore, the composition and mass proportion of the electrolytic aluminum waste in step 1 are: lithium 1%-1.1%, aluminum 12.2-13.0%, sodium 11.0-12.0%, iron 0.8-0.9%, calcium 1.5-2.0%, magnesium 0.24-0.26%, silicon <0.1%, fluorine 13.0-13.5%, sulfur 0.14-0.15%, manganese <0.1%, carbon >45%, and the rest is water.
[0016] Furthermore, the size of the electrolytic aluminum waste after crushing in step 1 is 1-10 cm.
[0017] Furthermore, in step 3, the slurry liquid-solid ratio of water to carbon removal material in the leaching process is 3-5:1, the mass ratio of carbon removal material to grinding balls is 1:1-1.5, the leaching agent is 98% sulfuric acid, the leaching temperature is 60-90°C, and the leaching time is 1-3h.
[0018] Furthermore, in step 4, the oxidant in the first stage of impurity removal is hydrogen peroxide, sodium chlorate, sodium hypochlorite, chlorine, air, and oxygen, the impurity removal temperature is 55-70°C, the alkali is a sodium hydroxide solution with a mass concentration of 5-20%, and the reaction time is 1-5h; the reaction time in the second stage of impurity removal is 1-5h, the decalcifying agent is oxalic acid, and the amount of the decalcifying agent added is 0.05%-0.1% of the electrolytic aluminum waste.
[0019] Furthermore, the temperature of the freezing crystallization in step 5 is -10°C to 10°C.
[0020] Furthermore, the heating temperature in step 6 is 90-100°C.
[0021] Furthermore, in step 7, the mass ratio of pure water to crude lithium carbonate is 9-10:1, and the pressure of the introduced CO2 gas is 0.1-0.2 MPa.
[0022] Furthermore, the temperature of the heating crystallization in step 7 is 90-100°C.
[0023] Among them, the mechanical strengthening leaching kettle used in step 3 includes a kettle body, a jacket, a tank cover, a liquid adding port, a stirring device and grinding balls, the jacket is coated on the outside of the kettle body, and a heating tube is provided in the jacket, the tank cover is located above the kettle body, and the tank cover is provided with a liquid adding port; the stirring device includes a motor, a reducer, a stirring shaft and a stirring paddle outside the stirring shaft, the motor and the reducer are located on the tank cover, the stirring shaft is connected to the motor and the reducer, the stirring shaft and the stirring paddle are located in the kettle body, and a plurality of grinding balls are placed in the kettle body, and the grinding balls are zirconia balls.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] (1) The electrolytic aluminum waste of the present invention is first calcined or burned to remove most of the carbon therein, so that the lithium extraction processing capacity can be increased by almost one-fold, and the concentration of the lithium solution can be increased by about one-fold, which greatly reduces the processing difficulty and cost and improves the lithium recovery rate and processing efficiency.
[0026] (2) The present invention controls the pH value of the leaching process to 3.0-4.0, so that the lithium in the electrolytic aluminum waste is dissolved, and most of the aluminum, iron, sodium, fluorine, etc. are not dissolved but remain in the leached residue, thereby reducing the amount of leaching acid used and greatly reducing the amount of alkali used for impurity removal. The slag filtering performance is good, and the sodium content in the lithium solution after impurity removal is greatly reduced. Only one denitration is required to meet the requirements, reducing the burden of each process, and reducing the cost of lithium extraction and the difficulty of operation. Since the aluminum content in the material is very high, the sodium content of the lithium solution after impurity removal is relatively high. By controlling the acidity of the leachate, the leaching of aluminum is inhibited, thereby reducing the loss of lithium caused by the adsorption of lithium by aluminum hydroxide in a colloidal state during alkali impurity removal.
[0027] (3) The present invention uses mechanical strengthening to strengthen leaching, solves the problem of high hardness and difficulty in fine grinding of the material, and uses mechanical strengthening to simultaneously grind and leach, increase the surface activity of the material, increase the active points of the material, thereby improving the treatment efficiency of electrolytic aluminum waste and the lithium extraction rate. The lithium leaching rate can reach more than 95%, the leaching conditions are mild, and the treatment efficiency is high. The carbon therein can be used as fuel, and most of the leached residue is cryolite, which can be used later.
[0028] (4) The lithium leaching solution of the present invention is subjected to two-stage impurity removal, wherein the first stage removes aluminum impurities, and the second stage removes other impurities such as iron, manganese, and calcium. The main products of the two stages of impurity removal are different and are processed separately. In the two-stage impurity removal process, oxalic acid is used as a decalcifying agent instead of conventional ion exchange resin, which can avoid the generation of excessive wastewater and the problem of easy scaling of ion exchange resin in sulfuric acid system, so that calcium can be removed efficiently and the system operates smoothly.
[0029] The method of the invention can effectively extract lithium from electrolytic aluminum waste to prepare battery-grade lithium carbonate. The main component of the leached slag is cryolite, which can be utilized with good economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The embodiments of the present invention are further described below with reference to the accompanying drawings, in which:
[0031] Figure 1 Shown is a process flow chart of the present invention;
[0032] Figure 2 The cross-sectional view and top view of the device structure of the mechanically enhanced leaching kettle are shown.
[0033] Among them, 1-motor, 2-reducer, 3-tank cover, 4-kettle body, 5-stirring shaft, 6-stirring paddle, 7-jacket, 8-grinding ball, 9-heating tube, 10-valve, 11-liquid filling port, 12-hinge, 13-slurry. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below through specific embodiments in conjunction with the accompanying drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0035] The mechanical strengthening leaching kettle includes a kettle body 4, a jacket 7, a tank cover 3, a liquid adding port 11, a stirring device and a grinding ball 8. The jacket 7 is coated on the outside of the kettle body 4, and a heating tube 9 is arranged in the jacket. The tank cover 3 is located above the kettle body 4, and two liquid adding ports 11 are arranged on the tank cover 3; the stirring device includes a motor 1, a reducer 2, a stirring shaft 5 and a stirring paddle 6 outside the stirring shaft. The motor 1 and the reducer 2 are located on the tank cover 3, and the stirring shaft 5 is connected to the motor 1 and the reducer 2. The stirring shaft 5 and the stirring paddle 6 are located in the kettle body 4. A plurality of grinding balls 8 are placed in the kettle body 4, and the grinding balls 8 are zirconium oxide balls, which are mixed with the slurry 13. A valve 10 is also arranged on the outlet pipeline below the kettle body 4. When the amount of slag in the system is small, a filter cloth can be installed on the pipeline below for filtering. The tank cover 3 is a semi-open tank cover, which is divided into two parts. The two parts are connected by a hinge 12 to achieve semi-opening, in order to facilitate the placement and removal of the grinding balls.
[0036] A method for preparing battery-grade lithium carbonate from electrolytic aluminum waste, comprising the following steps:
[0037] Step 1: Use a crusher or manually crush the electrolytic aluminum waste with a carbon content of more than 45% and an aluminum content of more than 10 times the lithium content. The size of the crushed electrolytic aluminum waste is 1-10 cm; the composition and mass proportion of the electrolytic aluminum waste are: lithium 1%-1.1%, aluminum 12.2-13.0%, sodium 11.0-12.0%, iron 0.8-0.9%, calcium 1.5-2.0%, magnesium 0.24-0.26%, silicon <0.1%, fluorine 13.0-13.5%, sulfur 0.14-0.15%, manganese <0.1%, carbon >45%, and the rest is water.
[0038] Step 2: calcining the crushed electrolytic aluminum waste at a high temperature of 550-1600°C for 0.5-5h to remove the carbon therein, and then cooling and coarse grinding to a particle size of 1-5mm to obtain a decarbonized material;
[0039] Step 3: Mechanically strengthen the acid leaching of the carbon removal material: Finely grind and selectively leach the carbon removal material in a mechanically strengthened leaching kettle, adjust the leaching pH value to 3.0-4.0, filter to obtain the leachate and leaching residue, filter the leaching residue and wash it twice before stacking, and return the leaching residue washing water to the leaching process; the slurry liquid-solid ratio of the carbon removal material to water during the leaching process is 3-5:1, the mass ratio of the carbon removal material to the grinding ball is 1:1-1.5, the leaching agent is 98% sulfuric acid, the leaching temperature is 60-90°C, and the leaching time is 1-3h. The leaching kettle is connected to an absorption device, and the absorption liquid in the absorption device is a dilute alkali solution to absorb the fluorine and acid mist generated during the leaching process.
[0040] 2LiF+H2SO4→Li2SO4+2HF↑
[0041] 2Na3AlF6+6H2SO4→3Na2SO4+Al2(SO4)3+6HF↑
[0042] Fe+H2SO4→FeSO4+H2↑
[0043] Step 4: performing two-stage impurity removal, wherein the first stage impurity removal process is: adding an oxidant to the first stage leaching solution, and then adding alkali to adjust the pH value to 4.5-5.0, filtering to obtain a filtrate and a filter residue; the oxidant in the first stage impurity removal process is hydrogen peroxide, sodium chlorate, sodium hypochlorite, chlorine, air, oxygen, the impurity removal temperature is 55-70° C., the alkali is a sodium hydroxide solution with a mass concentration of 5-20%, and the reaction time is 1-5 hours;
[0044] 2FeSO4+H2SO4+H2O2→Fe2(SO4)3+2H2O (chemical equation with hydrogen peroxide as oxidant)
[0045] Al2(SO4)3+6NaOH→3Na2SO4+2Al(OH)3↓
[0046] Fe2(SO4)3+6NaOH→3Na2SO4+2Fe(OH)3↓
[0047] The second stage impurity removal process is: add a decalcifying agent to the filtrate, then add alkali to adjust the pH value to 12.0-13.0, and filter to obtain a lithium-containing filtrate and impurity filter residue; the reaction time in the second stage impurity removal process is 1-5h, and the decalcifying agent is, and the amount of the decalcifying agent added is 0.05%-0.1% of the electrolytic aluminum waste.
[0048] Mn 2+ +2NaOH→2Na + +Mn(OH)2↓
[0049] H2C2O4+Ca 2+ →CaC2O4↓+2H +
[0050] Mg 2+ +2NaOH→2Na + +Mg(OH)2↓
[0051] Step 5: Heat and concentrate the lithium-containing filtrate, and then perform a freeze crystallization to obtain a denitrified liquid; the freeze crystallization temperature is -10°C-10°C to remove sodium sulfate.
[0052] Step 6: Add sodium carbonate solution to the denitrified liquid under heating conditions, and filter the precipitate to obtain crude lithium carbonate; the heating temperature is 90-100°C.
[0053] Li2SO4+Na2CO3→Li2CO3↓+2Na2SO4
[0054] Step 7: Dissolve the crude sodium carbonate in pure water and introduce CO2 gas into the solution. When the crude sodium carbonate is completely dissolved, filter it accurately to obtain a lithium carbonate solution. Heat it for crystallization, filter it, wash it, and dry it to obtain battery-grade lithium carbonate. The mass ratio of pure water to crude lithium carbonate is 9-10:1, the pressure of the CO2 gas introduced is 0.1-0.2MPa, and the temperature of heating crystallization is 90-100℃.
[0055] The specific embodiments are as follows:
[0056] The electrolytic aluminum scrap used in the following examples is in the form of hard blocks, with a carbon content of nearly half. The main components of the material are shown in Table 1.
[0057] Table 1 Composition and content of electrolytic aluminum waste
[0058]
[0059] Example 1
[0060] (1) Take a certain amount of electrolytic aluminum waste and crush it into small pieces of about 5 cm.
[0061] (2) Weigh 4000 g of the sieved material, put it into a crucible, and place it in a calcining furnace at a calcination temperature of 700°C for 5 hours. Cool it to room temperature, take out the material and initially crush it into small pieces of 1-5 mm.
[0062] (3) The material after carbon removal is added to a mechanically enhanced leaching kettle, and the slurry liquid-solid ratio with water is 5:1. Zirconia balls are added in a weight ratio of 1:1. Heating and stirring are turned on, and the leaching is heated to 80°C. 98% sulfuric acid is added to adjust the pH value to 3.5. The leaching is carried out for 2 hours. After leaching, the leaching liquid and leaching residue are obtained after filtration. The leaching residue is washed twice and then stored. The washing water of the leaching residue is returned to the leaching kettle. The leaching kettle is connected to an absorption device. The absorption liquid is a dilute alkali solution to absorb the HF gas generated during the leaching process. The lithium leaching rate is 99.39%, the iron leaching rate is 35.35%, and the aluminum leaching rate is only about 2.11%.
[0063] (4) Impurity removal: The leachate is subjected to two-stage impurity removal. The first stage of impurity removal is as follows: 1.2 times the theoretical amount of hydrogen peroxide is added to the leachate, followed by 5% sodium hydroxide to adjust the pH value to 4.5, the reaction temperature is maintained at 60°C, the reaction time is 4 hours, the filtrate and filter residue are obtained by filtration, the filter residue is slurried and washed twice, the filtrate is subjected to two-stage impurity removal, 2g of decalcifying agent oxalic acid is added, and then 5% sodium hydroxide is added to adjust the pH value to 12.5, the reaction time is 3 hours, the lithium-containing filtrate and impurity filter residue are obtained by filtration, and the filter residue is stored.
[0064] (5) Concentration and denitrification: The lithium-containing filtrate is heated and concentrated, and then cooled to 0°C for a period of freezing and crystallizing sodium sulfate to obtain a denitrified liquid.
[0065] (6) Lithium precipitation: Sodium carbonate is added to the denitrified liquid at 90°C to precipitate crude lithium carbonate.
[0066] (7) Add 10 times the mass of pure water to the crude lithium carbonate to dissolve it, then introduce CO2 gas at a pressure of 0.1 MPa, and accurately filter after all the lithium carbonate is dissolved to obtain a lithium carbonate solution. Heat the lithium solution to a slightly boiling temperature (90-100°C) for crystallization, filter, wash, and dry to obtain battery-grade lithium carbonate.
[0067] Example 2
[0068] (1) Take a certain amount of electrolytic aluminum waste and crush it into small pieces of about 5 cm.
[0069] (2) Weigh 1000 g of the sieved material, put it into a crucible, and place it in a calcining furnace at a calcination temperature of 1000°C for 3 hours. Cool it to room temperature, take out the material and initially crush it into small pieces of 1-5 mm.
[0070] (3) The decarbonized material is added to a mechanically enhanced leaching kettle, and the slurry liquid-to-solid ratio with water is 5:1. Zirconia balls are added at a weight ratio of 1:1.1. The heating and stirring are turned on, and the leaching is heated to 60°C. 98% sulfuric acid is added to adjust the pH value to 3.0. The leaching is carried out for 1 hour. After leaching, the leaching liquid and leaching residue are obtained after filtration. The leaching residue is washed twice and then stored. The leaching residue washing water is returned to the leaching process. The lithium leaching rate is 99.52%, the iron leaching rate is 36.77%, and the aluminum leaching rate is only 2.02%.
[0071] (4) Impurity removal: The leachate is subjected to two-stage impurity removal. The first stage of impurity removal is as follows: 1.1 times the theoretical amount of sodium chlorate is added to the leachate, followed by 10% sodium hydroxide to adjust the pH value to 4.5, the reaction temperature is maintained at 70°C, the reaction time is 2 hours, the filtrate and filter residue are obtained by filtration, the filter residue is slurried and washed twice, the filtrate is subjected to two-stage impurity removal, 1 g of decalcifying agent oxalic acid is added, and then 10% sodium hydroxide is added to adjust the pH value to 12.0, the reaction time is 5 hours, the lithium-containing filtrate and impurity filter residue are obtained by filtration, and the filter residue is stored.
[0072] (5) Concentration and denitrification: The lithium-containing filtrate is heated and concentrated, and then cooled to 10°C for a period of freezing and crystallizing sodium sulfate to obtain a denitrified liquid.
[0073] (6) Lithium precipitation: Sodium carbonate is added to the denitrified liquid at 95°C to precipitate crude lithium carbonate.
[0074] (7) Add 9 times the mass of pure water to the crude lithium carbonate to dissolve it, then introduce CO2 gas at a pressure of 0.2 MPa. After all the lithium carbonate is dissolved, fine filtration is performed to obtain a lithium carbonate solution. The lithium solution is heated to a slightly boiling temperature (90-100°C) for crystallization, and filtered, washed, and dried to obtain battery-grade lithium carbonate.
[0075] Example 3
[0076] (1) Take a certain amount of electrolytic aluminum waste and crush it into small pieces of about 5 cm.
[0077] (2) Weigh 15,000 g of the sieved material, put it into a crucible, and place it in a calcining furnace at a calcination temperature of 1,600°C for 5 hours. Cool it to room temperature, take out the material and initially crush it into small pieces of 1-5 mm.
[0078] (3) The decarbonized material is added to a mechanically enhanced leaching kettle, and the slurry liquid-to-solid ratio with water is 3:1. Zirconia balls are added at a weight ratio of 1:1.5. The heating and stirring are turned on, and the leaching is heated to 90°C. 98% sulfuric acid is added to adjust the pH value to 4.0. The leaching is carried out for 3 hours. After leaching, the leaching liquid and leaching residue are obtained after filtration. The leaching residue is washed twice and then stored. The leaching residue washing water is returned to the leaching process. The lithium leaching rate is 99.02%, the iron leaching rate is 36.52%, and the aluminum leaching rate is only 2.00%.
[0079] (4) Impurity removal: The leachate is subjected to two-stage impurity removal. The first stage of impurity removal is as follows: oxygen is introduced into the leachate to oxidize all the divalent iron in the lithium solution into trivalent iron, and then 20% sodium hydroxide is added to adjust the pH value to 4.5. The reaction temperature is maintained at 65° C. The reaction time is 5 h. The filtrate and filter residue are obtained by filtration. The filter residue is slurried and washed twice. The filtrate is subjected to two-stage impurity removal. 10 g of decalcifying agent oxalic acid is added, and then 20% sodium hydroxide is added to adjust the pH value to 13.0. The reaction time is 2 h. The lithium-containing filtrate and impurity filter residue are obtained by filtration, and the filter residue is stored.
[0080] (5) Concentration and denitrification: The lithium-containing filtrate is heated and concentrated, and then cooled to -10°C for a period of freezing and crystallizing sodium sulfate to obtain a denitrified liquid.
[0081] (6) Lithium precipitation: Sodium carbonate is added to the denitrified liquid at 98°C to precipitate crude lithium carbonate.
[0082] (7) Add 10 times the mass of pure water to the crude lithium carbonate to dissolve it, then introduce CO2 gas at a pressure of 0.2 MPa, and then accurately filter after all the lithium carbonate is dissolved to obtain a lithium carbonate solution. The lithium solution is heated to a slightly boiling temperature (90-100°C) for crystallization, and filtered, washed, and dried to obtain battery-grade lithium carbonate.
[0083] Comparative Example 1
[0084] (1) Take a certain amount of electrolytic aluminum waste and crush it into small pieces of about 5 cm.
[0085] (2) Weigh 4000 g of the sieved material, put it into a crucible, and place it in a calcining furnace at a calcination temperature of 700°C for 5 hours. Cool it to room temperature, take out the material and initially crush it into small pieces of 1-5 mm.
[0086] (3) The decarbonized material is added to the leaching kettle, and the slurry liquid-solid ratio with water is 5:1. The heating and stirring are turned on, and the leaching is heated to 80°C. 98% sulfuric acid is added to adjust the pH value to 3.5. The leaching is carried out for 2 hours. After leaching, the leaching liquid and leaching residue are obtained after filtration. The leaching residue is washed twice and then stored. The leaching residue washing water is returned to the leaching kettle. The leaching kettle is connected to an absorption device. The absorption liquid is a dilute alkali solution to absorb the HF gas generated during the leaching process. The lithium leaching rate is 89.52%, the iron leaching rate is 34.12%, and the aluminum leaching rate is only 1.95%.
[0087] (4) Impurity removal: add 5% sodium hydroxide to adjust the pH value to 12.5, maintain the reaction temperature at 60°C, and the reaction time is 5 h. Filter to obtain the filtrate and filter residue, and slurry the filter residue and wash it twice.
[0088] (5) Concentration and denitrification: The filtrate is heated and concentrated, and then the sodium sulfate is crystallized by freezing to obtain the denitrified liquid.
[0089] (6) Lithium precipitation: Sodium carbonate is added to the denitrified liquid to precipitate crude lithium carbonate.
[0090] (7) Add 10 times the mass of pure water to the crude lithium carbonate to dissolve it, then introduce CO2 gas at a pressure of 0.1 MPa to dissolve all the lithium carbonate and then filter it accurately to obtain a lithium carbonate solution. Heat the lithium solution to a slight boil (90-100°C) for crystallization, filter it, wash it, and dry it to obtain lithium carbonate.
[0091] Table 2 Composition of the final lithium carbonate product in the embodiments and comparative examples
[0092]
[0093] Some exemplary embodiments of the present invention are described above. It can be understood that the above embodiments are only used to explain the present invention and do not constitute a limitation on the protection scope of the present invention. The features in these embodiments can be recombined in a suitable manner, and the scheme obtained thereby is still within the protection scope required by the present invention. Based on the above embodiments, all other embodiments obtained by those skilled in the art without making creative work, that is, all modifications, equivalent substitutions and improvements made within the spirit and principles of this application, fall within the protection scope required by the present invention.
Claims
1. A mechanically enhanced leaching kettle, characterized in that: It includes a kettle body, a jacket, a tank cover, a liquid adding port, a stirring device and grinding balls. The jacket is coated on the outside of the kettle body and a heating tube is arranged inside the jacket. The tank cover is located above the kettle body and is provided with a liquid adding port. The stirring device includes a motor, a reducer, a stirring shaft and a stirring paddle outside the stirring shaft. The motor and the reducer are located on the tank cover. The stirring shaft is connected to the motor and the reducer. The stirring shaft and the stirring paddle are located in the kettle body. A plurality of grinding balls are placed in the kettle body, and the grinding balls are zirconia balls.
2. A method for mechanically strengthening lithium extraction from electrolytic aluminum waste, characterized in that: The following steps are involved: Step 1: crushing the electrolytic aluminum waste with a carbon content of more than 45% and an aluminum content of more than 10 times the lithium content; Step 2: calcining the crushed electrolytic aluminum waste at a high temperature of 550-1600°C for 0.5-5h to remove the carbon therein, and then cooling and coarse grinding to a particle size of 1-5mm to obtain a decarbonized material; Step 3: subjecting the decarbonized material to mechanical enhanced acid leaching: finely grinding and selectively leaching the decarbonized material in a mechanical enhanced leaching kettle equipped with grinding balls, adjusting the leaching pH value to 3.0-4.0, and filtering to obtain a leachate and a leaching residue; Step 4: performing two-stage impurity removal, wherein the first stage impurity removal process is: adding an oxidant to the leaching solution, then adding alkali to adjust the pH value to 4.5-5.0, filtering to obtain a filtrate and a filter residue; the second stage impurity removal process is: adding a decalcifying agent to the filtrate, then adding alkali to adjust the pH value to 12.0-13.0, filtering to obtain a lithium-containing filtrate and an impurity filter residue; Step 5: heating and concentrating the lithium-containing filtrate, and then freezing and crystallizing it to obtain a denitrified liquid; Step 6: adding sodium carbonate solution to the denitrified liquid under heating conditions, precipitating and filtering to obtain crude lithium carbonate; Step 7: Dissolve the crude sodium carbonate in pure water and introduce CO2 gas into the solution. When the crude sodium carbonate is completely dissolved, filter it precisely to obtain a lithium carbonate solution. Heat, crystallize, filter, wash and dry to obtain battery-grade lithium carbonate.
3. The method for mechanically strengthening lithium extraction from electrolytic aluminum waste according to claim 2, characterized in that: The composition and mass proportion of the electrolytic aluminum waste in step 1 are: lithium 1%-1.1%, aluminum 12.2-13.0%, sodium 11.0-12.0%, iron 0.8-0.9%, calcium 1.5-2.0%, magnesium 0.24-0.26%, silicon <0.1%, fluorine 13.0-13.5%, sulfur 0.14-0.15%, manganese <0.1%, carbon >45%, and the rest is water.
4. The method for mechanically strengthening lithium extraction from electrolytic aluminum waste according to claim 2, characterized in that: The material is the electrolytic aluminum waste crushed in step 1, with a size of 1-10 cm.
5. The method for mechanically strengthening lithium extraction from electrolytic aluminum waste according to claim 2, characterized in that: In step 3, the slurry liquid-solid ratio of water to carbon removal material in the leaching process is 3-5:1, the mass ratio of carbon removal material to grinding balls is 1:1-1.5, the leaching agent is 98% sulfuric acid, the leaching temperature is 60-90°C, and the leaching time is 1-3h.
6. The method for mechanically strengthening lithium extraction from electrolytic aluminum waste according to claim 2, characterized in that: In step 4, the oxidant in the first stage impurity removal process is hydrogen peroxide, sodium chlorate, sodium hypochlorite, chlorine, air, and oxygen, the impurity removal temperature is 55-70°C, the alkali is a sodium hydroxide solution with a mass concentration of 5-20%, and the reaction time is 1-5h; the reaction time in the second stage impurity removal process is 1-5h, the decalcifying agent is oxalic acid, and the amount of the decalcifying agent added is 0.05%-0.1% of the electrolytic aluminum waste.
7. The method for mechanically strengthening lithium extraction from electrolytic aluminum waste according to claim 2, characterized in that: The temperature of the freezing crystallization in step 5 is -10°C to 10°C.
8. The method for mechanically strengthening lithium extraction from electrolytic aluminum waste according to claim 2, characterized in that: The heating temperature in step 6 is 90-100°C.
9. The method for mechanically strengthening lithium extraction from electrolytic aluminum waste according to claim 2, characterized in that: In step 7, the mass ratio of pure water to crude lithium carbonate is 9-10:1, and the pressure of the introduced CO2 gas is 0.1-0.2MPa.
10. The method for mechanically strengthening lithium extraction from electrolytic aluminum waste according to claim 2, characterized in that: The temperature of heating crystallization in step 7 is 90-100°C.